Recidivism and Reentry: The Role of Individual Coping Styles. (January 2019) - LaCourse, Ashleigh; Listwan, Shelley Johnson; Reid, Shannon; Hartman, Jennifer L.
The high rate of recidivism among those reentering the community post incarceration can be partially attributed to various barriers to reentry, including unemployment, financial difficulties, and mental illness. Learning to cope with these barriers is demanding and stressful for many people. The current article examines whether individual coping styles could act as a significant predictor of recidivism. Utilizing a cross-sectional data set collected from previously incarcerated individuals, this study examines the relationship between individual coping styles and arrest or reincarceration. Results from this study indicate a relationship between coping and arrest. Implications from this study are noteworthy given that our understanding of coping can increase the ability of the correctional staff to reduce later recidivism in the community.